The Effect of Employee Engagement and Organizational Culture on Employee Performance Through Turnover Intention As An Intervening Variable - Dany Fauzan Ramadhan (Riwayat: Educational Journal of History and Humanities, 2023)
In its operation, a company has various resources that are useful for the sustainability of the company and one of them is human resources. To guarantee and see the quality of human resources in a company, it can be seen from how the turnover rate is in a company. The occurrence of increased turnover is something that can harm the company. In 2020 and 2021, PT. Indo Kordsa experienced an increase in employee turnover and this study aims to examine what factors influence employee intention to move using retention strategies in which there is employee engagement with additional organizational culture variables and their effects on employee performance. This study used quantitative methods by distributing online surveys through google form to 173 respondents. The data analysis used is using the help of SPSS tools and Sobel test tools. The research findings indicate that Employee Engagement has a significant negative effect on Turnover Intention, but it has a significant positive effect on Employee Performance. Meanwhile, Organizational Culture does not have a significant effect on Turnover Intention, but it has a significant positive effect on Employee Performance. Additionally, this study also examines the mediation of Turnover Intention on the relationship between Employee Engagement and Employee Performance, as well as the relationship between Organizational Culture and Employee Performance. The analysis results show that Turnover Intention does not mediate the influence of Employee Engagement on Employee Performance. Similarly, Turnover Intention does not mediate the influence of Organizational Culture on Employee Performance.  In conclusion, improving Employee Engagement can help enhance Employee Performance, while a good Organizational Culture also plays a role in improving Employee Performance. However, Turnover Intention does not act as a mediator in the relationship between Employee Engagement and Employee Performance, as well as between Organizational Culture and Employee Performance.